First molecular detection of Cytauxzoon felis and Babesia sp. in ticks collected from wildlife in Atwemonom bushmeat market of Ghana and their potential veterinary health implications - Emmanuel Kwame Amoako; Seth Offei Addo; Richard Odoi-Teye Malm; Caleb Kobina Danso-Coffie; Elinam Adzo Agbobli; Joseph Kwame Benne; Patience Akosua Darko; Eric Behene; Sandra Abankwa Kwarteng; Samuel Kweku Dadzie; Langbong Bimi; Ben Adu Gyan; et al. (Veterinary Research Communications, 2026)

Molecular detection of tick-borne pathogens of zoonotic and veterinary importance in ticks from hunting dogs in Ghana - Seth Offei Addo; Selma Nurudeen Salley; Millie-Cindy Aba Aude Koffi; Christopher Nii Laryea Tawiah-Mensah; Richard Odoi-Teye Malm; Patrick Kwasi Obuam; Ewurabena Oduma Duker; Jessica Dufie Boakye; Gayheart Deladem Agbotse; Danielle Ladzekpo; Samuel K. Dadzie (Veterinary Research Communications, 2026)

First record and molecular identification of Amblyomma geoemydae and Haemaphysalis campanulata parasitizing wildlife in Ashanti Region, Ghana - Seth Offei Addo; Patrick Kwasi Obuam; Christopher Nii Laryea Tawiah-Mensah; Richard Odoi-Teye Malm; Stacy Amoah; Ewurabena Oduma Duker; Jessica Dufie Boakye; Gayheart Deladem Agbotse; Sandra Abankwa Kwarteng (Veterinary Research Communications, 2026)

Risk factors affecting the feeding site predilection of ticks on cattle in Ghana - Seth Offei Addo; Ronald Essah Bentil; Mba-tihssommah Mosore; Eric Behene; Julian Adinkrah; Janice Tagoe; Clara Yeboah; Bernice Olivia Ama Baako; Dorcas Atibila; Sandra Abankwa Kwarteng; Kwaku Poku-Asante; Ellis Owusu-Darbo; et al. (Experimental and Applied Acarology, 2024)
Ticks are important disease vectors affecting animal health and causing substantial economic loss, especially in the tropics and subtropics. To examine the tick burden of cattle and associated risk factors for tick infestation, ticks were collected from 388 cattle within five regions in Ghana. Most of the cattle were males (50.3%) and generally older than 3 years (65%). Of the animals sampled, 2187 ticks were collected with a mean tick burden of 5.6 ticks per cattle, and the average tick burden on the udder/scrotum being significantly higher than in the anal region (Generalized Linear Mix Model [GLMM], p = 0.01197). The tick species identified were predominantly Amblyomma variegatum (42.6%) and Hyalomma rufipes (26.2%). High proportions of cattle examined were found to have A. variegatum infesting the udder/scrotum. Furthermore, H. rufipes infested mostly the anal region compared to other examined body parts (OR 14.8, 95% CI 8.6–25.4, p < 0.001). Using the GLMM, tick abundance was found to be significantly higher in cattle older than 3 years. The tick burden in the udder/scrotum was higher than that from the chest and leg/thigh of the cattle (GLMM, p < 0.05). The tick burden at the anal region was also significantly higher than the leg/thigh and chest. This study indicates that the preferred attachment sites of ticks on cattle are species-dependent and effective treatment with acaricides should take into consideration the udder/scrotum and anal regions as well as prioritizing older cattle.

Molecular identification of Crimean-Congo haemorrhagic fever virus in Hyalomma rufipes and Amblyomma variegatum in the Upper East Region of Ghana - Seth Offei Addo; Ronald Essah Bentil; Charlotte Adwoa Addae; Bernice Olivia Ama Baako; Kevin Nii Yartey; Jane Ansah‑Owusu; Christopher Nii Laryea Tawiah-Mensah; Bright Agbodzi; Selassie Kumordjie; Clara Yeboah; Victor Asoala; James C. Dunford; et al. (Archives of Virology, 2024)

Molecular identification of cattle ticks in the Greater Accra Region of Ghana: a high occurrence of Rhipicephalus microplus - Christopher Nii Laryea Tawiah-Mensah; Seth Offei Addo; Jane Ansah-Owusu; Mufeez Abudu; Richard Odoi-Teye Malm; Kevin Nii Yartey; Daniel Oduro; Jewelna Akorli; Samuel K. Dadzie (Experimental and Applied Acarology, 2024)

Occurrence of Rickettsia spp. and Coxiella burnetii in ixodid ticks in Kassena-Nankana, Ghana - Seth Offei Addo; Ronald Essah Bentil; Bernice Olivia Ama Baako; Kevin Nii Yartey; Eric Behene; Benjamin Asiamah; Abena Akyeamaa Nyarko; Victor Asoala; Mohamed Sallam; Suzanne Mate; James C. Dunford; John Asiedu Larbi; et al. (Experimental and Applied Acarology, 2023)

First record of Rhipicephalus (Boophilus) microplus in Ghana, a potential risk to livestock production - Seth Offei Addo; Ronald Essah Bentil; Bernice Olivia Ama Baako; Charlotte Adwoa Addae; John Asiedu Larbi; Philip Kweku Baidoo; Michael David Wilson; Victor Asoala; Daniel Oduro; Suzanne Mate; Joseph W. Diclaro II; Samuel K. Dadzie (Experimental and Applied Acarology, 2023)

Molecular survey of Anaplasma and Ehrlichia species in livestock ticks from Kassena-Nankana, Ghana; with a first report of Anaplasma capra and Ehrlichia minasensis - Seth Offei Addo; Bernice Olivia Ama Baako; Ronald Essah Bentil; Charlotte Adwoa Addae; Eric Behene; Victor Asoala; Mohamed Sallam; Suzanne Mate; James C. Dunford; John Asiedu Larbi; Philip Kweku Baidoo; Michael David Wilson; et al. (Archives of Microbiology, 2023)